Evaluation of Metarhizium brunneum F52 (Hypocreales: Clavicipitaceae) for Control of Japanese Beetle Larvae in Turfgrass. Issue 4 (2nd July 2015) - Behle, Robert W.; Richmond, Douglas S.; Jackson, Mark A.; Dunlap, Christopher A.
Abstract : Experimental and commercial preparations of Metarhizium brunneum (Petch) strain F52 were evaluated for control of Japanese beetle, Popillia japonica Newman (Coleoptera: Scarbaeidae), larvae (white grubs) in the laboratory and under field conditions. Experimental preparations consisted of granule and liquid formulations made using in vitro produced microsclerotia, which are intended to produce infective conidial spores after application. These formulations were compared against commercial insecticides (imidacloprid and trichlorfon), and commercial formulations of M. brunneum F52 (Met 52) containing only conidia. Field-collected grubs were susceptible to infection in a dosage-dependent relationship when exposed to potting soil treated with experimental microsclerotia granules in the laboratory. The LC50 for field-collected larvae was 14.2 mg of granules per cup (∼15 g granules/m 2 ). Field plots treated with experimental and commercial formulations of M. brunneum F52 after 10 September (targeting second and third instar grubs) had significantly lower grub densities compared with untreated plots, providing 38.6–69.2% control, which sometimes equaled levels of control with chemical insecticides. Fungal treatments made prior to 21 August provided 14.3–69.3% control, although grub densities resulting from these treatments were often not significantly lower than those in untreated control plots. By comparison, chemical insecticide treatments provide 68–100% grub control, often providing better control when applied earlier in the season. In conclusion, P. japonica larvae are susceptible to infection by M. brunneum, and grub densities were reduced most consistently by fall applications targeting later instars.